DEBIT AIR SUNGAI MELANCAR DI KAWASAN LINDUNG GUNUNG LONCEK KECAMATAN ANJONGAN KABUPATEN PONTIANAK - Sutrisnawati, Ana; Handayani, Dwi; Latifah, Siti (Universitas Tanjungpura, 2015)
In addition, water is non biological factor from the forest that has an important role, especially for people who lived in that area. The availability of the water in one area have to be describe to explore that the potential and availability of the water in the area. For Melancar river, there’s no research about the availability of the river water. This research aims to study water debit of Melancar river in protected area of Gunung Loncek in Kecamatan Anjongan Kabupaten Pontianak in rainy and dry. It also explain the condition of vegetation in Gunung Loncek. The results show that water debit of Melancar river in dry days was 0,0278 m3/s and the debit in rainy days was 0,0392 m3/s. The function of the forest in Gunung Loncek area is important to manage water availability, it is shown by the difference of the Melancar river’s debit value between rainy and dry days is not too far evently it is significantly different. The availability of the Melancar river’s water is still good enough and it still can supply people who lived in Melancar river area for their daily used. Keywords : Water Debit, The Melancar River, availability.